Development of Papan Nilai Tempat Learning Media to Improve Students’ Critical Thinking Skills - Syahrani Yumna Irfani; Nirwana Anas (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to develop the PANIPAT (Papan Nilai Tempat) learning media to improve students’ critical thinking skills that is valid, practical, and effective. This study is based on the importance of students’ critical thinking skills, as with critical thinking skills, students can think rationally and make the best choices for themselves.This study used the Research and Development (R&D) method with the ADDIE development model. The instruments used included expert validation sheets, questionnaires, and critical thinking skills test sheets. The results of this study showed that the PANIPAT media was considered highly feasible for use, with an average validation score of 87.15%, categorized as feasible. The average score from teacher and student questionnaires was 96.4%, which is classified as very practical. In addition, the N-Gain result was 66%, which is classified as effective. The conclusion of this study indicates that the PANIPAT media is capable of making a significant contribution to improving students’ critical thinking skills, particularly in mathematics learning